Are Histologic Studies of Adenotonsillectomy Really Necessary? - Rebechi,Giseli (2013)
Introduction  In most ear, nose, and throat services, it is routine to send the material extracted from tonsillectomy for histologic study to research malignancy, to analyze suspect material, or to provide medical-legal documentation. Recent studies have shown that this routine analysis is dispensable. Objective  To evaluate the actual need and perform a cost–benefit analysis of routine histopathologic examination in tonsillectomy with no signs or symptoms of malignancy. Methods  A retrospective observational study evaluated the charts of patients undergoing adenotonsillectomy, tonsillectomy, or adenoidectomy from January 2008 to September 2009 at the Institute of Otorhinolaryngology CEMA-SP. Costs of this test for the public health system were analyzed and the literature reviewed. Results  We studied 281 patients between 2 and 22 years of age; 142 (50.5%) were male and 139 (49.5%) were female. Of the surgeries, 201 were adenotonsillectomies (71.5%), 41 were tonsillectomies (14.5%), and 39 were adenoidectomies (14%). The most common indication for surgery was recurrent infection (63.3%). None of study patients had clinical suspicion of malignancy. The tests showed a cost of R$20.03 per tonsil analyzed. Conclusion  Routine histopathologic examination in patients undergoing adenotonsillectomy with no signs or symptoms of malignancy is dispensable and increases the cost of the surgeries.